ARTIGO 103-A DA CONSTITUIÇÃO: A INTRODUÇÃO DA SÚMULA VINCULANTE NO ORDENAMENTO PÁTRIO - Lima, Carlos Eduardo Oliveira; Marques, Edson Rodrigues; Aguiar, Rodrigo Souza (REVISTA DA AGU, 2007)
Não possui.